Tourism and Guidebooks in the Activities of Academic Staff at the Faculty of Fine Art at Stefan Batory University in Vilnius - Kania, Agnieszka (Respectus Philologicus, 2021)
Stefan Batory University in Vilnius was established in 1919 as a regional entity to carry out scientific research and develop Polish academic education. One of its faculties – the Faculty of Fine Arts (1930–1939) – gathered charismatic and popular artists, historians and architects. Among them, two professors – Juliusz Kłos (1888–1933) and Marian Morelowski – published the guidebooks for Vilnius and Wileńszczyzna region (Wilno. Przewodnik krajoznawczy, 1937; Zarys sztuki wileńskiej z przewodnikiem po zabytkiem między Niemnem a Dźwiną, 1939). The book written by Kłos gained popularity and was often purchased by the tourists who visited Vilnius. The aim of the article is to determine the main methodology, historical approaches and working styles of both authors. Moreover, the paper involves their attitude towards developing tourism, cultural heritage and historical research. The article also involves the main ideas of artistic education professors had and how much tourism was involved in the whole education process for them.